Breeding Practices, Flock Productivity, and Strategies for Enhancing the Performance of Indigenous Chicken Genetic Resources - Kugonza, Donald Rugira; Kayitesi, Aline; Nakkazi, Christine; Okot, Marion Wilfred (Discoveries in Agriculture and Food Sciences, 2025)
Farmer knowledge of breeding practices, incubation, and disease management strategies for local chickens was studied in 120 households in the Gulu and Kiryandongo regions of Uganda using a questionnaire, administered during one-to-one interviews. We found that farmers were randomly sampled from each of the eight sub-counties studied. Local chickens in both locations reached sexual maturity at six months for both cocks and hens. The overall mean number of egg clutches/bird/year was 3.21±0.07, and eggs per clutch were 13.07±0.22. Breeding stock was mostly acquired through purchases for both districts, and 97.5% of all the farmers carry out selective breeding. Farmers in the study area used a variety of criteria when selecting hens and cocks as breeding stock. Body size for both cocks (index = 0.51) and hens (index = 0.38) were a key trait in the selection, and specifically for cocks, body height ranked second as a good physical trait for selection, and is a marker/indicator trait for body weight. In females, farmers rank egg production, mothering, and hatching ability highly, too. All farmers relied on natural incubation to hatch eggs, but the facilities differed widely among respondents in both districts (P<0.001). All farmers in Kiryandongo provided overnight shelters, differing from Gulu (P<0.001) where 43.3% of households had chickens perching on trees. Newcastle disease was the major disease reported by respondents in both districts. Capacity building of chicken farmers would go a long way to improve local chicken management and thereby, productivity.